The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1093/jmedent/29.6.980
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Borrelia burgdorferi in Laboratory-Reared Ixodes dammini (Acari: Ixodidae) Fed on Experimentally Inoculated White-Tailed Deer

Abstract: Larvae and nymphs of Ixodes dammini Spielman, Piesman, Clifford & Corwin from a laboratory colony were fed on two white-tailed deer, Odocoileus virginianus (Zimmerman) inoculated with either the SH2-82 or JD-1 strains of Borrelia burgdorferi Johnson, Schmid, Hyde, Steigerwalt & Brenner. Ticks were exposed to one deer 43 and 69 d after inoculation of the spirochete and to a second deer 35 and 61 d after inoculation. Polymerase chain reaction assays amplified the 158 bp OspA DNA target sequence in 11.1% (n = 9) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The overall infection rates in ticks were 33.3% in 2006, 6.9% in 2007 and 5.2% in 2008. The capacity of deer to act as reservoirs for B. burgdorferi s.l., is controversial [33,34]. However, our results clearly support the idea that wild cervids are incompetent reservoirs.…”
Section: Discussionsupporting
confidence: 83%
“…The overall infection rates in ticks were 33.3% in 2006, 6.9% in 2007 and 5.2% in 2008. The capacity of deer to act as reservoirs for B. burgdorferi s.l., is controversial [33,34]. However, our results clearly support the idea that wild cervids are incompetent reservoirs.…”
Section: Discussionsupporting
confidence: 83%
“…Ixodes ticks were obtained from wild sika deer (Cervus nippon yesoensis Heude, 1884) and the midgut was cultured in Barbour-Stoenner-Kelly (BSK) medium (2) previously described (6 can serve as a source of at least two geographic strains of B. burgdorferi to I. dammini larvae and nymphs for at least several weeks (14). Our results presented here do not settle the controversy as to whether sika deer serve as reservoirs for B. burgdorferi complex.…”
Section: Introductionmentioning
confidence: 75%
“…Lane et al (12) suggest that additional studies are needed to determine more precisely the reservoir competence of white-tailed deer for B. burgdorferi. Recently, Oliver et al (14) reported that experimentally inoculated deer can serve as a source of B. burgdorferito Ixodes dammini larvae and nymphs for at least several weeks.…”
mentioning
confidence: 99%
“…Deer are generally considered not to transmit B. burgdorferi ( s.l. ) [25, 26] and deer sera has been found to be borreliacidal [27]; however some studies suggest potential for co-feeding transmission [28, 29]. Deer provide blood meals to ticks and are important in many areas as tick reproduction hosts, feeding reproductively active adult female ticks [30].…”
Section: Introductionmentioning
confidence: 99%